A new species of Oncopeltus Stål, 1868 (Heteroptera: Lygaeidae) in the nominate subgenus from Ecuador - Faúndez, Eduardo I.; Rocca, Javiera R. (Zootaxa, 2017)
Oncopeltus Stål is a lygaeine genus currently comprising 39 species classified in two subgenera (Slater & O’Donnell, 1995). Oncopeltus is distributed in both hemispheres in tropical and temperate areas. Species on this genus are commonly known as milkweed bugs, because of their trophic association with plants in the family Apocynaceae (Scudder & Duffey, 1971). From these plants, the bugs sequester cardenolides making them unpalatable for predators (Duffey & Scudder, 1972). These habits are also accompanied with their brightly reddish coloration, which has been interpreted as aposematism (Duffey & Scudder, 1972, O’Rourke, 1979; Faúndez et al., 2016). As these bugs attack several plants in the subfamily Asclepiadoideae; they have an economic impact on several ornamentally used species, and may sometimes be considered as garden pests (Faúndez & Rocca, 2016; Faúndez et al., 2016). Species of this group are also well known for generating some natural hybrids (O’Rourke, 1979); because of this, their systematic treatment at specific level has been confused, and the identity of several taxa remain unclear. The purpose of this contribution is to describe a new species in this genus from Ecuador.